When Is the Government Transfer Multiplier Large? - Giambattista, Eric (Elsevier, 2018)
Transfers to individuals were a larger part of the 2009 US stimulus package than government purchases. Using a two-agent New Keynesian model, we show analytically that the multiplier on targeted transfers to financially constrained households is (i) larger than the purchase multiplier if the zero lower bound (ZLB) binds, and (ii) is more sensitive to the degree of monetary accommodation of inflation. Targeted transfers provide the same boost to demand as purchases, but lower aggregate supply relative to purchases, as those receiving transfers want to work less. When the aggregate demand curve inverts — such as when the ZLB binds — the extra inflation from lower supply boosts the multiplier. We show this result also holds quantitatively in a medium-scale version of the model.